Financial Attitude and Personality Impact on Street Vendor’s Financial Behavior - Indah, Aprilina; Hariasih, Misti (Academia Open, 2022)
This quantitative research aimed to investigate the impact of financial knowledge, financial attitudes, and personality on financial management behavior among street vendors in Sidoarjo. The study utilized a saturated sampling technique, gathering responses from 90 fruit street vendors in Taman Pinang Indah, Sidoarjo Regency. The research variables included financial knowledge (X1), financial attitude (X2), personality (X3), and financial management behavior (y). Primary data was collected using a Likert scale questionnaire, which underwent validity and reliability tests. The study revealed that financial knowledge demonstrated a negative relationship and had no significant influence on financial management behavior. Conversely, financial attitude exhibited a positive relationship and significantly impacted financial management behavior. Additionally, personality exhibited a positive relationship and a significant effect on financial management behavior. These findings contribute to our understanding of the factors shaping financial behavior among street vendors, thereby offering valuable implications for financial education programs and interventions. Highlights: Financial attitude and personality influence financial management behavior among street vendors. This quantitative study explores the relationship between financial attitude, personality, and financial management behavior. The findings provide valuable insights for improving financial education programs for street vendors. Keywords: financial attitude, personality, financial management behavior, street vendors, quantitative study.